Forests and water : a thematic study prepared in the framework of the Global Forest Resources Assessment 2005 - Hamilton, Lawrence S.; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2008)
This study explains the role of forests in the hydrological cycle, w ith a particular focus on critical, "red flag" forest situations such a s mountainous or steep terrain, river and coastal areas and swamp ecosy stems, as well as the special case of mountainous small islands. It add resses the protection of municipal water supplies and emerging systems of payment for watershed services.--Publisher's description.
Introduction -- Forests and water quantity -- Forests and water qual ity -- "Red flag" forest situations -- The special case of mountainous small islands -- Payments for environmental services -- Recommendations .
Includes bibliographical references.
Also available online.
Keywords: Forest influences; Watersheds; Forest hydrology; Forest management; Watershed management